Analysis of Transparent and Accountable Financial Management Through the Online-Based Village Financial Management System (SISKEUDES) in Pilohayanga Barat Village - Usu, Idrus; Lamuda, Ilyas; Buntayo, Isnawaty (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study aims to analyze village financial management in a transparent and accountable manner through the online-based Village Financial System (SISKEUDES) application in Pilohayanga Barat Village. The background of this research stems from the importance of good village governance in accordance with the principles of transparency, accountability, participation, and effectiveness. The research method used is a qualitative method with a descriptive approach. Data collection techniques include in-depth interviews with village officials and direct observation of the SISKEUDES application usage process. The research sample consists of village officials involved in financial management, selected using a purposive sampling technique. The results of the study indicate that the implementation of the SISKEUDES application has a positive impact on the village financial management process, from planning and administration to reporting. The use of this application improves work efficiency, accelerates the preparation of financial reports, and minimizes errors in record-keeping. Additionally, the real-time system in SISKEUDES allows for direct budget monitoring by relevant parties, thereby enhancing accountability and transparency. The challenges found in implementing this application include the limited human resources with inadequate technological skills and unstable internet connectivity. However, these challenges can be addressed through regular training conducted by the local government and BPKP.